The Nexus Between Green HRM Practices And Organizational Sustainability Performance: Evidence From Indonesia - Nugraha, Andhyka Tyaz; Sunarti, Sunarti; Makitsuna, Farhand (Jurnal Manajemen Indonesia, 2024)
Green Human Resource Management (GHRM) is an management approach that pursues to integrate environmental perspective into conventional human resource activities. This approach is characterized by a systematic and scheduled synchronization with the organization’s environmental priorities, which is viewed as providing a balanced perspective that aligns employees with the organization’s environmental policy. Introducing, enforcing, and embracing systemic changes among employees is one of the most important GHRM objectives, as green-based activities are frequently difficult to implement. GHRM practices serve a crucial role in the context of organizational sustainable development in achieving sustainability objectives. Prior research has evaluated GHRM as a unidimensional or second-order construct consisting of three or four dimensions. However, the current study extends previous research by identifying six categories of GHRM practices and empirically evaluating the impact of each of these elements on corporate sustainability. The study collected data from 347 HR directors working in Indonesian organizations and analyzed the data using SmartPLS 3.2.8. The findings revealed that three out of the six GHRM activities were significantly related to organizational sustainability performance. The study offers theoretical and practical implications for potential researchers and HR managers, particularly in the Indonesian context.